Uses of Activated Carbon Columns for Solid Phase Extraction Studies Prior to Determinations of Traces Heavy Metal Ions by Flame Atomic Absorption Spectrometry - Soylak , Mustafa; Elci, Latif; Dogan, Mehmet (Asian Journal of Chemistry, 2012)
Column solid phase extractions of trace heavy metal ions from various matrices including natural water, urine, etc. have been widely used by using activated carbon. The separation/preconcentration methods developed for the atomic absorption spectrometric determination of trace heavy metals in our laboratory based on activated carbon column are reviewed in the present study.